Deficiency of STING Promotes Collagen-Specific Antibody Production and B Cell Survival in Collagen-Induced Arthritis - Tansakul, Mookmanee; Thim-uam, Arthid; Saethang, Thammakorn; Makjaroen, Jiradej; Wongprom, Benjawan; Pisitkun, Trairak; Pisitkun, Prapaporn (Frontiers in Immunology, 2020)
The levels of interferon-alpha are high in the serum and synovial fluid of rheumatoid arthritis (RA) patients. Activation of the stimulator of type I interferon genes (STING) mediates the productions of type I interferon and promotes chronic inflammation. STING plays a significant role in autoimmune lupus mice. However, the function of STING in collagen-induced arthritis (CIA) model has never been described. This study aimed to test the function of STING in CIA. The Sting-deficient mice developed arthritis comparable to WT mice. The levels of anti-collagen antibody from Sting-deficient mice were significantly higher than the WT mice. The B cells derived from Sting-deficient mice showed better survival than WT mice in response to the B cell receptor (BCR) stimulation. Activation of STING also induced B cell death, especially in activated B cells. This study demonstrated that the inhibition of STING promotes anti-collagen antibodies and B cell survival, which suggested that STING acts as a negative regulator of B cell function in the CIA model.